Adherence to a priori and a posteriori dietary patterns and risk of Parkinson’s disease: a systematic review and meta-analysis of observational studies - Zhang, Rong; Shu, Long; Zhu, Qin; Li, Nan (Frontiers in Nutrition, 2025)
BackgroundAlthough studies have reported the associations between certain dietary patterns and the risk of Parkinson’s disease, these findings are limited and inconclusive. Herein, we carried out a systematic review and meta-analysis of observational studies to search for the associations between a priori and a posteriori dietary patterns and the risk of developing Parkinson’s disease.MethodsWe systematically searched PubMed, Web of Science, Scopus, and China National Knowledge Infrastructure from database inception to January 2025 to clarify eligible observational studies investigating the links between whole dietary patterns and risk of Parkinson’s disease. Combined relative risks (RRs) and 95% confidence intervals (CIs) were calculated for the highest versus lowest categories of dietary patterns in relation to Parkinson’s disease risk. The Cochran’s Q test and I-squared (I2) statistic were used to assess statistical heterogeneity among the included studies.ResultsIn total, 11 studies (five cohort, three case–control, and 3 cross-sectional studies) with 326,751 participants and 2,524 cases were included in this meta-analysis. The pooled analyses showed that adherence to the Mediterranean diet, healthy dietary index, and healthy dietary pattern were associated with a decreased risk of Parkinson’s disease (RR = 0.87; 95%CI: 0.78–0.97, p = 0.017; RR = 0.76; 95%CI: 0.65–0.91, p = 0.002; RR = 0.76; 95%CI: 0.62–0.93; p = 0.007, respectively). Additionally, the results showed that high adherence to the Western dietary pattern was associated with an increased risk of Parkinson’s disease (RR = 1.54; 95%CI: 1.10–2.15; p = 0.011).ConclusionOverall, our results demonstrate that adherence to the Mediterranean diet, a healthy dietary index, and a healthy dietary pattern were associated with a reduced risk of Parkinson’s disease, while the Western dietary pattern was linked to an increased risk of Parkinson’s disease. Further well-designed prospective studies and randomized controlled trials are required to confirm these findings.